Analisis sektor industri manufaktur di Indonesia - Nurhayani, Nurhayani (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
because it can increase economic growth. This study aims to analyze the factors that affect the manufacturing industry sector in Indonesia. The analytical method used in this research is descriptive analysis and quantitative analysis. Overall, from 2000 - 2020, the average development of the manufacturing industry was 12.67 percent, labor averaged 2.4 percent, investment averaged 9.2 and inflation averaged 8.6 percent. This study uses multiple linear regression analysis using the period 2000-2020. The results of the study show that the variable Number of Labor and investment has an effect on the manufacturing industry in Indonesia for the period 2000-2020, while inflation has no effect.